ECONOMICAL USE OF WATER RESOURCES IN IRRIGATION OF AGRICULTURAL CROPS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article presents the results of studies devoted to water-saving irrigation technology on steep slopes and clarifies the elements of irrigation technology for contour irrigation in the conditions of southern Uzbekistan.